Landscape of Loci and Candidate Genes for Muscle Fatty Acid Composition in Pigs Revealed by Multiple Population Association Analysis - Zhang, Junjie; Zhang, Yifeng; Gong, Huanfa; Cui, Leilei; Ma, Junwu; Chen, Congying; Ai, Huashui; Xiao, Shijun; Huang, Lusheng; Yang, Bin (Frontiers in Genetics, 2019)
Genome wide association analyses in diverse populations can identify complex trait loci that are specifically present in one population or shared across multiple populations, which help to better understand the genetic architecture of complex traits in a broader genetic context. In this study, we conducted GWAS and meta-analysis for 38 fatty acid composition traits with 12-19 million imputed genome sequence SNPs in 2446 pigs from six populations, encompassing White Duroc × Erhualian F2, Sutai, Duroc-Landrace-Yorkshire (DLY) three-way cross, Laiwu, Erhualian and Bamaxiang pigs that were originally genotyped with 60 K or 1.4 million SNP chips. The analyses uncovered 285 lead SNPs (P < 5 × 10-8), among which 78 locate more than 1 Mb to the lead chip SNPs were considered as novel, largely augmented the landscape of loci for porcine muscle fatty acid composition. Meta-analysis enhanced the association significance at loci near FADS2, ABCD2, ELOVL5, ELOVL6, ELOVL7, SCD and THRSP genes, suggesting possible existence of population shared mutations underlying these loci. Further haplotype analysis at SCD loci identified a shared 3.7 kb haplotype in F2, Sutai and DLY pigs showing consistent effects of decreasing C18:0 contents in the three populations. In contrast, at FASN loci, we found an Erhualian specific haplotype explaining the population specific association signals in Erhualian pigs. This study refines our understanding on landscape of loci and candidate genes for fatty acid composition traits of pigs.